The Related Factors of unmet neet phenomena in fertile coule in desa pasir matogu kecamatan angkola muaratail kabupaten tapanuli selatan - siregar, nurelilasari (Universitas Aufa Royhan, 2021)
The high number of unmet needs is a population phenomenon that becomes an important aspect that needs to be considered in the development of the family planning movement in the future. The purpose of the study was to analyze factors related to the occurrence of Unmet Need in Couples of Childbearing Age (PUS) in Pasir Matogu Village, Angkola Muaratais District, South Tapanuli District in 2021. This research is analytical with a cross-sectional design. The population in this study was all women of childbearing age couples who were married, had children, and lived together with 104 husbands, which was sampled by 51 people. The collected data is analyzed using the Chi-Square test. The results showed that income, employment status, parity, knowledge of KB and support from husbands were significantly related to the incidence of unmet family planning needs. It is recommended for kb officers in the working area of Puskesmas Pintu Padang, especially in Pasir Matogu Village, so that efforts to apply the KB program need to be improved and focused on unmet need groups. Efforts that can be made is by providing KIE for both husband and wife through home visits by each village midwife.